I personaggi di La Gilda del Mac Mahon di Giovanni Testori: fra (neo)realismo e (neo)espressionismo - Janusz, Joanna (Romanica Silesiana)
The study concerns the analysis of the works of Giovanni Testori contained in the volume La Gilda del Mac Mahon (1959). From the chronological, epistemological and aesthetic point of view, Testori’s debut works are characteristic for two different literary tendencies of writing: neorealist and expressionistic. The neorealist traditions coming into play in Testori’s works include themes (difficult situation of the people living in Milan’s suburbs), and forms of expression (low point of view, spoken style-popular). Testori in a very personal and original way weaves together the narrative neorealist elements with those of the new aesthetics, the expressionistic vanguard which is present to the maximum extent in his theatrical works. The expressionism of Testori is represented by the subjective and partial representation of the story and most of all by the typology of the protagonist (a young protagonist who is naked, that is presented in his most intimate actions: oppression and solitude, alienation, anti-bourgeois revolt, desperate search of the better life). The expressionistic power of the stories is amplified by their episodic structure, responsible for the effect of fragmentariness and discontinuity of the representation of the world that is restless and frenetic. Key words: Giovanni Testori, neorealism, expressionism.